Water Column Stratification and Mixing Events in Narragansett Bay During Winter and Spring - Andrews, James Emery (DigitalCommons@URI, 1997)
We deployed a buoy in the West Passage of Narragansett Bay, approximately one km east of Hope Island, within a bathymetric depression of approximately twice the surrounding water depth. The buoy contained an onboard logging computer and had three YSI-600 instruments, each capable of measuring temperature, salinity, dissolved oxygen, pH and pressure, logging at three different depths in the water column at a 20 minute sampling interval. The first deployment started on 6 January 1997 and lasted 18 days before problems required retrieving the buoy. Additionally, problems with the salinity sensors in this deployment made it impossible to use most of the salinity data. We fixed the salinity and electronic problems, modified the mooring system, and redeployed the buoy on 10 March 1997. We collected data for two months in this second deployment, until 8 May 1997. Using the temperature, salinity (when available), dissolved oxygen and pressure data from these deployments, we investigated the relationship between physical stratification as determined by density, and oxygen variations. We also used the predicted tides, observed tides from the moored, bottom instrument, wind data from the GSO Pier and from T. F. Green Airport, USGS stream flow data and NOAA-NWS precipitation data from T.F. Green Airport to investigate forcing relationships for the physical stratification and destratification cycles. Using the difference between the bottom and surface parameters as an index for stratification, we determined that the density related stratification results in increased vertical oxygen gradients, and that a 1 kg m-3 difference between surface and bottom in density is accompanied by approximately a 10 % saturation difference over the same depth. The stratification cycles are related to the spring-neap tidal cycles for extended periods, and to strong wind forcing for shorter time scales. Large fresh water inputs can affect stratification as a result of estuarine entrainment whereby the vertical salinity gradient increases. This ...